A Discrete-Event and Hybrid Simulation Framework Based on SimEvents for Intelligent Transportation System Analysis ⁎. Issue 7 (2018) - Zhang, Yue; Cassandras, Christos G.; Li, Wei; Mosterman, Pieter J.
Abstract: Intelligent transportation systems combine physical elements with cyber components based on information and communication technologies and the use of control methodologies for Connected Automated Vehicles (CAVs). Intelligent transportation systems, therefore, contain event-driven dynamics along with time-driven dynamics. The hybrid nature of such systems motivates the development of new simulation platforms in order to test and evaluate their effectiveness. A discrete-event and hybrid simulation framework based on SimEvents is introduced within which these systems can be studied at the microscopic level. This framework enables users to apply different control strategies as well as communication protocols for CAVs and to carry out performance analysis of proposed algorithms by authoring customized discrete-event and hybrid systems that include various design paradigms such as entity flow, graphical programming, and object-oriented programming in MATLAB ® . These paradigms provide users with the flexibility to select or combine modeling elements for achieving complex goals as the demonstrated scenarios in the paper illustrate. The framework spans multiple toolboxes including MATLAB, Simulink ®, and SimEvents ® .